1983
DOI: 10.1139/t83-032
|View full text |Cite
|
Sign up to set email alerts
|

Leda clay from deep boreholes at Hawkesbury, Ontario. Part I: Geology and geotechnique

Abstract: The geologic and geotechnical characteristics of thick soft Champlain Sea clay deposits at Hawkesbury, Ontario are presented in this paper. A second paper will deal with the mineralogy and geochemistry of the same deposits.A westerly clay plain at ~50 m and an easterly plain at ~75 m elevation occur in the area. Preconsolidation pressure versus depth curves obtained for clays from both deposits show marked preconsolidation near the top and bottom drainage boundaries and nearly normally consolidated conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(20 citation statements)
references
References 8 publications
4
16
0
Order By: Relevance
“…Field measurements of the overconsolidation ratio at various depths ( $ upto60 m) from 31 sites in Quebec revealed that eastern-Canada sensitive clays are mainly preconsolidated (Demers and Lerouiel 2002). Similar conclusions were also reported by Crawford (1961) and Quigley et al (1983) for the shallower depths ( $ upto 35 m) of Leda clay from the Ottawa valley. In this study, an approximate trend of overconsolidation profile for the ORHO site was developed on the basis of the reported trends from the field observations and laboratory consolidation tests by Rasmussen (2012).…”
Section: Validation Of Calibrated Modelssupporting
confidence: 81%
See 2 more Smart Citations
“…Field measurements of the overconsolidation ratio at various depths ( $ upto60 m) from 31 sites in Quebec revealed that eastern-Canada sensitive clays are mainly preconsolidated (Demers and Lerouiel 2002). Similar conclusions were also reported by Crawford (1961) and Quigley et al (1983) for the shallower depths ( $ upto 35 m) of Leda clay from the Ottawa valley. In this study, an approximate trend of overconsolidation profile for the ORHO site was developed on the basis of the reported trends from the field observations and laboratory consolidation tests by Rasmussen (2012).…”
Section: Validation Of Calibrated Modelssupporting
confidence: 81%
“…Several laboratory tests have revealed that inter-particle cementation bonds govern the strength and deformation characteristics of Leda clay within in situ overburden stress range. Results of one-dimensional consolidation tests performed on Leda clay samples in different studies have admittedly indicated very stiff behaviour in the pre-yield stress region with brittle response around the pre-consolidation pressure (Mitchell 1970;Vaid et al 1979;Quigley et al 1983). Moreover, the strain-rate dependent feature of the stress-compressibility relationship of the sensitive clay from eastern Canada, with noticeable contribution of secondary consolidation, was investigated by Leroueil et al (1983) and Vaid et al (1979).…”
Section: Properties Of Leda Clay From Laboratory Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…The principal mineral sediment underlying the peatland is the Champlain Sea Clay (National Capital Commission 1974), also known as the Leda Clay, which is about 35 m thick in the vicinity. This was deposited 12.8 thousand years ago during a glaciomarine inundation, after the Wisconsinan ice sheet melted (Gadd 1963(Gadd , 1986Quigley et al 1983). Later episodes of freshwater regimes left the abandoned river channels now occupied by the peatland (Belanger and Harrison 1977).…”
Section: Mer Bleuementioning
confidence: 99%
“…One outstanding feature of the modelling approach is the capacity for predictions to be made well into the future, thereby demonstrating the likely impacts of current practice on the environment and future generations. The validity of predictions based on mathematical modelling of contaminant transport has been investigated and shown to be good for time periods measured in decades (Quigley and Rowe 1986) and even for time periods of thousands of years (Desaulniers et al 1981;Quigley et al 1983;Rowe and Sawicki 1992).…”
Section: Introductionmentioning
confidence: 99%